(untitled) (American Journal of Pedagogical and Educational Research, 2023)
This article presents examples of critic Bahadir Karimov’s life, work and creativity. The characteristics of the work "Ruhiyat alifbosi" and its place in our literary studies are explained. Bahadir Karimov’s role in the revolution is also described.